A relação registro/avaliação no ciclo da juventude: possibilidades e limites na construção de uma prática educativa inovadora - Marcia Ambrosio Rodrigues Resende (2004)
This is a dissertation that aims to check the relation between evaluation / registers, conceived and utilized as methods by teachers in a moment of pedagogical innovation: the implementation of the Escola Plural within the youth cycle. Such methodolocial proceedings, utilized and materialized in schools registers, were observed in order to seek for the meaning that they hold, both by teachers and students.The focus of this research is based in two main questions regarding the validity of the evaluative proceedings (tests, assessments) as a pedagogical tool: the continuity of its use and the procedures that must be made, both by teachers and students, to accommodate the new paradigm. It means that we checked on how those actors were dealing with such a new conception of evaluation presented by the Escola Plural program: being formative, continuous, dinamic and investigative. This research was carried on in Escola Municipal Paulo Mendes Campos school. A qualitative survey was made and a case study was adpoted as a methodological strategy. Such taken actions allowed us not only to peruse the situation but also to enhance its initial questions. A participant observation was made and throughout the process it was possible for this research to become dynamic and interfering, so to speak, in the actors reality. Also, a large gamut of data collecting was adopted which resulted into a much broader and complete analysis of the subject. The conclusion points to the fact that schools registers might be instruments to help us knowing students reality since it shows the pedagogical constructions that each student is capable of doing. However, as a counterpoint, it can reflects schools pedagogical boundaries, for when students and teachers do not participate in the process, the assessment analysis is in jeopardy.